2005
DOI: 10.1016/j.ymthe.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hepatic Delivery and Expression from a Recombinant Adeno-associated Virus 8 Pseudotyped α1-Antitrypsin Vector

Abstract: alpha1-Antitrypsin (AAT) deficiency is a single-gene disorder in which a mutation in the AAT (approved symbol SERPINA1) gene (PI*Z) leads to misfolding of the protein, loss of the protective antiprotease effect of AAT for the lungs, and a toxic effect on hepatocytes. Optimal therapy for AAT deficiency will require a high percentage of hepatocyte transduction to be effective for liver and lung disease. Recently, rAAV genomes pseudotyped with capsids from serotypes 7 and 8 showed efficient hepatic transduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…19,32 Human Cell Lines The HEK-293 cell line (ATCC no. CRL-1573, Manassas, VA, USA) and the HepG2 liver cell line (ATCC no.…”
Section: Sirna-expressing Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…19,32 Human Cell Lines The HEK-293 cell line (ATCC no. CRL-1573, Manassas, VA, USA) and the HepG2 liver cell line (ATCC no.…”
Section: Sirna-expressing Constructsmentioning
confidence: 99%
“…[34][35][36][37] Injection has been described previously. 19 Work is carried out completely under a sterilized laminar flow hood in SPF animal facility. A portable rodent isoflourane machine is used at 3% mixture.…”
Section: Portal Vein Injection Of Raav8 Vectors In Z-aat Transgenic Micementioning
confidence: 99%
See 2 more Smart Citations
“…Studies in adult mice have shown that partial hepatectomy, which is associated with a burst of hepatocellular proliferation, leads to rapid loss of episomal vector genomes. [14][15][16] Essentially the same phenomenon is seen following vector delivery to neonatal mice, where high rates of hepatocellular proliferation result in almost complete clearance of episomal vector genomes within two doublings of liver mass occurring within the first 1-2 weeks of life. 17,18 A stable basal level of transgene expression, probably reflecting vector integration, persists thereafter in up to 8% of hepatocytes depending on the vector dose used.…”
Section: Impact Of Proliferation In Target Cell Populationsmentioning
confidence: 85%